2021
DOI: 10.11621/pir.2021.0403
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities in Primary School. How to Diagnose and Remediate the Difficulties with a Team Approach: The First Results

Abstract: Background. An important problem of our day is the significant increase in the number of learning-disabled pupils all over the world. This has led to the emergence of a new branch of neuropsychology — “school neuropsychology” or the “Neuropsychology of learning.” Objective. This paper analyzes the role and functions of a neuropsychologist in primary schools and the possibilities of his/her collaboration with other specialists in diagnosing children’s problems and organizing remediation for problematic kids. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…Such work guarantied positive emotions and attitude toward mathematical knowledge in children. This data supports the idea of the previous publication about positive effects of the work of young scholar in teams ( Glozman and Plotnikova, 2021 ; Sidneva et al, 2022 ). The study allows to think that introduction of mathematical knowledge might be presented as attractive and pleasant collective activity.…”
Section: Discussionsupporting
confidence: 90%
“…Such work guarantied positive emotions and attitude toward mathematical knowledge in children. This data supports the idea of the previous publication about positive effects of the work of young scholar in teams ( Glozman and Plotnikova, 2021 ; Sidneva et al, 2022 ). The study allows to think that introduction of mathematical knowledge might be presented as attractive and pleasant collective activity.…”
Section: Discussionsupporting
confidence: 90%
“…It has been observed that the social support levels of mothers whose children have been diagnosed with SLD and their attitudes towards coping with stress are statistically significantly different from the of mothers of undiagnosed children (Atalay, 2013). The presence of SLD negatively affects children's relationships with their families and communication with their peers, further aggravating the SLD level (Glozman & Plotnikova, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription skills (handwriting and spelling) may be assessed by various methods. We used methods developed by the Vygotsky-Luria school, which are currently successfully identifying children’s learning disabilities ( Akhutina and Pylaeva, 2012 ; Glozman and Plotnikova, 2021 ).…”
Section: Introductionmentioning
confidence: 99%